Risk Management Through an “Activity Contradictions” Lens: Exposure to Low Doses of Radiation in Nuclear Medicine - Lonceint, Romain; Bodéré, Françoise; Geffroy, Bénédicte (Frontiers in Medicine, 2019)
Risk management is a major concern for health organizations. In hospitals, it concerns both medical and occupational risks, particularly those related to exposure to ionizing radiation. Medical personnel represent 70% of workers exposed to ionizing radiation. The highest doses in the order of a few mSv are recorded in nuclear medicine departments. Nuclear medicine health professionals are thus exposed daily in the context of their work activity to low doses but whose effects remain uncertain. In the face of this situation of uncertainty, the precautionary approach prevails in the field of radiation protection. Thus, health professionals are called upon to treat the patient while protecting themselves from exposure to low doses of radioactivity. This research aims to understand the relationship of health professionals to the risks of exposure to low doses and how they combine the logic of patient care and cure with that of self-protection. It is based on a qualitative study of two embedded cases carried out in two units of a nuclear medicine department of a university hospital, combining two data collection methods: 23 interviews with various health professionals in the department and 10 weeks of observations of the work activity of these same professionals. The analysis of the data shows that the coexistence of care/cure and radiation protection logic is a source of contradictions for nuclear medicine professionals. The analysis of the results focuses on the identification and characterization of the different forms of contradictions inherent in working in the nuclear medicine department. The results show that the intensity of these contradictions varies according to four factors: phases (preparation, administration, patient installation and examination), type of medical act, patient behaviour and characteristics, and type of professionals. Finally, the results distinguish the different types of responses provided by health professionals to regulate these contradictions. These risk regulation strategies differ according to occupational groups and their relationship to risk.